2010
DOI: 10.1002/bdd.718
|View full text |Cite
|
Sign up to set email alerts
|

Effect of absorption site on the pharmacokinetics of sublingual asenapine in healthy male subjects

Abstract: Asenapine is a psychopharmacologic agent approved in the United States for the acute treatment of schizophrenia in adults and the acute treatment of manic or mixed episodes associated with bipolar I disorder with or without psychotic features in adults. It is pending approval for the treatment of schizophrenia and manic episodes associated with bipolar I disorder in Europe. Asenapine is administered as a sublingual formulation. To determine whether the pharmacokinetics of asenapine are impacted by placing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 9 publications
0
19
0
Order By: Relevance
“…Drinking water sooner than 10 minutes after administration of sublingual asenapine can reduce its bioavailability,2,26 with a 19% reduction in plasma exposure observed following water administration at two minutes. If placed elsewhere in the oral cavity, asenapine will still be absorbed, as demonstrated in an open-label, randomized, three-way crossover trial among healthy men who received single 5 mg doses of asenapine via sublingual, supralingual, and buccal routes,29 where with buccal administration (ie, “cheeking”) the plasma level exposure was almost 25% higher than for the sublingual route, and 6% lower with supralingual administration than with sublingual administration. These differences in exposure are smaller than the overall variability observed in studies, where overall exposure varied by 37%, with a mean interindividual variability of 26% and a mean intraindividual variability of 26% 26.…”
Section: Pharmacokinetics and Pharmacodynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Drinking water sooner than 10 minutes after administration of sublingual asenapine can reduce its bioavailability,2,26 with a 19% reduction in plasma exposure observed following water administration at two minutes. If placed elsewhere in the oral cavity, asenapine will still be absorbed, as demonstrated in an open-label, randomized, three-way crossover trial among healthy men who received single 5 mg doses of asenapine via sublingual, supralingual, and buccal routes,29 where with buccal administration (ie, “cheeking”) the plasma level exposure was almost 25% higher than for the sublingual route, and 6% lower with supralingual administration than with sublingual administration. These differences in exposure are smaller than the overall variability observed in studies, where overall exposure varied by 37%, with a mean interindividual variability of 26% and a mean intraindividual variability of 26% 26.…”
Section: Pharmacokinetics and Pharmacodynamicsmentioning
confidence: 99%
“…Directly asking patients about adverse effects, such as oral hypoesthesia, may yield higher rates. In healthy male subjects from a Phase I study of asenapine 5 mg,29 the most common adverse events were oral paresthesia (sublingual, 75.8%; supralingual, 55.9%; buccal, 45.7%) and somnolence (81.8%; 76.5%; 68.6%).…”
Section: Safety and Tolerabilitymentioning
confidence: 99%
“…For this reason, the manufacturer’s insert recommends that patients not eat or drink anything within 10 minutes following administration of the drug. However, Gerrits et al 15 has shown that consuming water at 5 minutes following a 5 mg dose of asenapine decreased the plasma levels by only 10%, and that consuming water 2 minutes following a similar dose lowered drug exposure by approximately 20%. 13 It is not likely that these differences in drug exposure are clinically meaningful, as the reductions in exposure are actually less than the mean interindividual exposure variability which is as high as 26% when administered with perfect adherence to US Food and Drug Administration (FDA) guidelines.…”
Section: Pharmacologymentioning
confidence: 99%
“…At doses above the saturation solubility, bioavailability becomes dependent on the distribution equilibrium and also on contact time in the mouth 57. Compared with the sublingual route, asenapine exposure is 24% higher with buccal and supralingual administration administration 58. However, the latter routes convey a risk of tooth decay.…”
Section: Review Of Pharmacology Mode Of Action and Pharmacokineticsmentioning
confidence: 99%